2014
DOI: 10.1186/1756-0500-7-246
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and waist/height ratio for prediction of severity of coronary artery disease

Abstract: BackgroundTo determine whether waist-to-height ratio correlates with coronary artery disease (CAD) severity better, than the body mass index (BMI) as assessed by coronary angiography in Bangladeshi population.MethodsThis cross sectional study was done on patients in Department of Cardiology in DMCH and those referred in the cath-lab of the Department of Cardiology for CAG during November 2009 to October 2010 involving 120 patients. They were divided into group-A (with coronary score ≥7) and group-B (coronary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 24 publications
6
26
0
3
Order By: Relevance
“…In Bangladesh, almost all of the studies reported an overwhelming majority of male patients. [17][18][19] Females were found to be more obese than male in the current study as well as in the other studies. [20][21] In comparison with Europeans, the mean stature of Bangladeshi counterparts is 1.3 cm to 11.8 cm shorter.…”
Section: Discussionsupporting
confidence: 69%
“…In Bangladesh, almost all of the studies reported an overwhelming majority of male patients. [17][18][19] Females were found to be more obese than male in the current study as well as in the other studies. [20][21] In comparison with Europeans, the mean stature of Bangladeshi counterparts is 1.3 cm to 11.8 cm shorter.…”
Section: Discussionsupporting
confidence: 69%
“…In Bangladesh, almost all of the studies reported an overwhelming majority of male patients. [17][18][19] Females were found to be more obese than male in the current study as well as in the other studies. [20][21] In comparison with Europeans, the mean stature In-hospital adverse outcomes after PCI was significantly higher in Group I.…”
Section: Discussionsupporting
confidence: 69%
“…Of the anthropometric parameters, WHtR yielded the highest positive correlation with CAD 25 . Th is was the fi rst study on the eff ect of WHtR on clinical severity and prognosis of acute STEMI.…”
Section: Discussionmentioning
confidence: 99%